Development of “Water Detective” Diorama in Islamic Education through Pancasila Student Profile Strengthening Project (P5) - Widiyono, Aan; Nuraini, Latifah; Chasannudin, Arif; Minardi, Joko; Jannah, Aulia Miftahul (Universitas Muhammadiyah Magelang, 2023)
Having high level human resources that globally competitive is very important in this era of constant changes. The limited use of concrete media contributes to the decline of efficiency, creativity, and involvement in the classes. The purpose of this research is to assess the feasibility and efficiency of various learning media. The ADDIE R&D model is used in this study. The results of the validation test by material and media experts shows a score of 33 out of 40 or 82.5%, which means that this product is